Atividade missionária e transformações : inconstância e variação entre os Boe-Bororo de Meruri-MT - Bello, Ligia Maria de Lana (2020)
This thesis is an ethnographic study on the presence of missionary activity among the Boe-Bororo, an Macro-Jê-speaking indigenous people, in Meruri village, located in the city of General Carneiro - MT. Above all, it aims to describe the ways in which the Boe Bororo view culture for themselves and for the others, outlining what they call a “cultural revival”. The Boe-Bororo people have a long experience of relations with members of the Sacred Heart of Jesus Mission, which in 2020 will complete 118 years of missionary activity in Meruri. More than a hundred years ago, the Boe-Bororo incorporated some values and aspects of the Christian religious message without rupturing with their own cosmology rearranging some events imposed by contact on their own terms.